Various Teaching Methods and Models of Virus Learning at High School and College Level: A Systematic Review - Hendro Gunadi; Suranto Suranto; Murni Ramli (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
The topic of viruses is closely related to the daily life and problems faced by students. The concept of viruses is considered difficult by students because they are abstract and contain many unfamiliar words. This research aimed to analyze various teaching methods and models of virus learning at the high school and college level and to find out the most suitable models or methods in learning virus concepts effectively. This study reviewed research articles published on online databases, such as Google Scholar, Eric, WorldCat, and ScienceDirect. Articles were selected using the PRISMA method with the keywords "virus concepts" and "high school" "biology education" published from 2011-2020. Matched articles from Google Scholar (N = 52), Eric (N = 5) Science Direct (N = 2) WorldCat (N = 4). The articles were selected based on the research focus according to the topic, there were 10 articles according to the criteria, methods, and results of articles by the objectives of this study and were analyzed. The results showed that virus concept learning in school can be done using various learning methods and models. The best learning methods and models in learning viral concepts are contextual ones such as problem-based learning and the use of learning media such as video games. The results of the article review show that the concept of viruses through contextual learning can improve students' understanding, learning outcomes, misconceptions, and critical thinking